2018
DOI: 10.1136/annrheumdis-2018-213464
|View full text |Cite
|
Sign up to set email alerts
|

Work participation in spondyloarthritis across countries: analysis from the ASAS-COMOSPA study

Abstract: Higher education level and higher country SE welfare are associated with a higher likelihood of keeping patients with SpA employed. Absenteeism and presenteeism are only associated with clinical but not with individual-level or country-level SE factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
11
1
3
Order By: Relevance
“…As in the ASAS-COMOSPA study, we found significant between-country variation in work participation [8]. There were no significant differences in employment status, absenteeism, presenteeism, overall work impairment, or their predictive factors across SpA phenotypes.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As in the ASAS-COMOSPA study, we found significant between-country variation in work participation [8]. There were no significant differences in employment status, absenteeism, presenteeism, overall work impairment, or their predictive factors across SpA phenotypes.…”
Section: Discussionsupporting
confidence: 56%
“…There are remarkable differences in work status and productivity costs even between neighbouring European countries despite comparable quality of care for chronic diseases [3,4]. Worldwide, country-level socioeconomic factors (e.g., healthcare expenditure) are associated with employment in SpA [8]; these often overlooked contextual factors are essential for understanding widespread inequality in disease outcomes. A prior study reported associations between individual-level factors (e.g., gender and education) and employment status [8], but how country-level factors modify the effect of individual-level socioeconomic factors remains an unmet research need.…”
Section: Introductionmentioning
confidence: 99%
“… 25 For example, manual workers experience more impact from axSpA on presenteeism, but also experience more beneficial effect of bDMARDs on presenteeism. 26 Country of residence (likely reflecting social security regulations, including income substitution) is another contextual determinant of variation in employment and sick leave rates across countries, 27 28 and may cause effect modification of interventions. 29 OMERACT proposed a classification of 12 contextual factor domains potentially relevant for WP outcomes 30 31 ( table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] Even more important than work disability is perhaps thinking of prequels to this often irreversible outcome, such as presenteeism and sick leave (SL). [5][6][7][8][9] The findings of studies to date that have sought to examine specifically SL, vary widely in the literature and across countries. [10][11][12] SL is to a large extent an individual's decision and also driven by the social security system of a country, aside from a disease-driven outcome; in this regard, personal contextual…”
Section: Introductionmentioning
confidence: 99%